HISTOMORPHOMETRIC ESTIMATION OF AGE FROM BONE SAMPLES OF NIGERIANS - Orupabo, C. D.; Oghenemavwe, L. E.; Diamond, T. E. (International Journal of Medicine and Medical Research, 2021)
Background. Age estimation is crucial in creating the biological profile of unknown skeletal remains and recently there is emphasis on the need to develop population specific forensic baseline data for easy identification of these remains. Objective. The aim of this study is to estimate age from the histomorphometric features of the bones of Nigerians. Methods. Fragments of non-pathologic bone samples were collected during orthopaedic procedures. Ground sections were prepared using Modified Frost’s manual method of bone preparation to determine the following histologic parameters; haversian canal diameter (HCD), primary and secondary osteons, number of osteon fragments and non-haversian canal as well as haversian canal area (HCA). 29 subjects aged 35 to 85 years old were used for the study. Bone fragments included samples from the femur, tibia, humerus, and the vertebrae. Data obtained were subjected to descriptive statistics, Pearson’s correlation, bivariate regression equation, Student t-test and analysis of variance (ANOVA). Results. The mean age for our population was 58.86 years old. ANOVA showed significant variation in the average HCD for the various regions: humerus=8.45±2.48, femur=7.09±4.06, tibia=8.70±2.52 and vertebrae=3.69±0.73. There was a strong inverse relationship between age and primary osteons. The total number of osteon fragments increased with age while total number of primary osteons and average HCD decreased with age. The HCA, though statistically insignificant, also decreased with age. Conclusion. Our findings show that three histomorphometric parameters showed significant correlation with age: osteon fragments (OS-f), primary osteons (OS-p) and HCD. The histomorphometric parameters were therefore relevant in age estimation. Objective: The aim of this study is to estimate age from the histologic features of the bones of Nigerians. Methods: Fragments of non-pathologic bone samples were collected during orthopaedic procedures. Ground sections were prepared using Modified Frost’s manual method of bone preparation to determine the following histologic parameters; haversian canal diameter (HCD), primary and secondary osteons, number of osteon fragments and non haversian canal as well as haversian canal area (HCA). 29 subjects aged 35 to 85 years were used for the study. Bone fragments included samples from the femur, tibia, humerus, and the vertebrae. Data obtained were subjected to descriptive statistics, Pearson’s correlation, bivariate regression equation, student t-test and Analysis of variance (ANOVA). Results: The mean age for our population was 58.86 years. ANOVA shows significant variation in the average HCD for the various regions: humerus=8.45±2.48, femur=7.09±4.06, tibia=8.70±2.52 and vertebrae=3.69±0.73. There is a strong inverse relationship between age and primary osteons. The total number of osteon fragments increased with age while total number of primary osteons and average HCD decreased with age. The HCA though statistically insignificant, also decreased with age. Conclusion: Our findings show that three histomorphometric parameters showed significant correlation with age: osteon fragments (OS-f), primary osteons (OS-p) and HCD. The histomorphometric parameters are therefore relevant in age estimation. Key words: Age estimation, Histomorphometric parameters, Nigerians, Forensics